Holocene thinning history of David Glacier, Antarctica - James Stutz II (2020)
The Antarctic Ice Sheet is a significant component of the Earth System, modulating Earth‘s sea level and climate. Present day and projected ice mass losses from Antarctica are of paramount concern to human populations in low-lying communities around the world. Ocean freshening from future ice discharge events also has the potential to destabilise global climate patterns. Over 40 years of satellite observations have tracked changes in ice mass, extent and thickness in Antarctica. However, ice sheets respond on timescales that range from annual to millennial, and a geologic perspective is needed to fully understand ice sheet response on timescales longer than a few decades. This research seeks to provide an improved understanding of Antarcticas future by constraining its past. I focus on one of the largest outlet glaciers in Antarctica, the David Glacier/Drygalski Ice Tongue system which drains the East Antarctic Ice Sheet, dissects the Transantarctic Mountains and discharges into the Ross Sea. I seek to answer two questions; (1) what is the timing and nature of David Glacier thinning since the Last Glacial Maximum approximately 20,000 years ago, and (2) what physical processes were responsible for the observed thinning? I answer these questions by mapping the terrestrial and marine geomorphology along the former margins and seaward extension of David Glacier, and by using surface exposure dating of bedrock and glacial erratics to constrain the timing of glacier thinning. I then use a numerical flowline model to identify the processes that drove glacier thinning and retreat. Surface exposure ages from bedrock and glacial erratics at field sites both upstream and downstream of the modern grounding line reveal that David Glacier thinned for two millennia during the mid-Holocene. Near the coast, this thinning occurred at ∼6.5 kya at a rapid rate of up to 2 m/yr. Upstream from the grounding line, the thinning was more gradual but occurred simultaneously with thinning downstream. The timing of glacial thinning at David ...